Interleukin-1 beta induces autophagy of mouse preimplantation embryos and improves blastocyst quality - Pan, Yangyang; Wang, Meng; Wang, Libin; Xu, Gengquan; Baloch, Abdul Rasheed; Kashif, Jam; Fan, Jiangfeng; Yu, Sijiu (Journal of cellular biochemistry, 2020)
Autophagy is one of the basic cellular mechanism during preimplantation development of mammalian embryos, and it plays crucial role in several physiological processes. It is induced by interleukin (IL)-1β in mammalian cells. Our present study shows that IL-1β is important for autophagy activation in embryo development. Our in vitro culture system analysis shows effect of IL-1β in medium on the development of mouse embryos and it was found to be concentration dependent. A preimplantation embryo culture using medium containing IL-1β did not improve cleavage and blastocyst development rates of mouse embryos; however, blastocyst quality was significantly improved by increasing total cell number, especially in supplementary 20 ng/mL IL-1β. Furthermore, autophagy activation mainly occurs in 2 to 4 cell embryo and blastocyst, 20 ng/mL IL-1β into culture medium can effectively enhance levels of messenger RNA and protein of autophagy-related-factors in 2 to 4 cell embryos and blastocyst, while these factors reduce in VGX-1027 (IL-1β inhibitor) groups that also reduce the quality of blastocyst. Effects of IL-1β on the development of embryo reduced in 20 ng/mL IL-1β supplemented group when 5 mM 3-methyladenine (3-MA) was also added, which used to inhibit autophagy activation in endogenous PtdIns3Ks signal pathway. Our current results show that exogenous IL-1β can effectively induce autophagy in mouse embryos at stages of 2 to 8 cell and blastocyst, that also help to improve the quality of blastocyst.
Keywords: Animals; Female; Autophagy; Embryo Culture Techniques; Embryo, Mammalian; ženské pohlaví; blastocysta; Mice; myši; Blastocyst; autofagie; Interleukin-1beta; Male; Embryonic Development; interleukin-1beta; zvířata; embryonální vývoj; mužské pohlaví; kultivace embrya; embryo savčí